PARAMETRIC STUDY OF NATURAL DIELECTRIC MATERIALS THICKNESS IN WAVEGUIDE ANTENNA MODE TE10 COASTAL RADAR 3 GHz ANTENNA - M. Reza Hidayat; Hidayat Ramdan; Handoko Rusiana Iskandar; Giri Angga Setia (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2021)
Manufacturing process was important in the development of antenna technology in order to obtain the antenna optimal performance. One of the approaches to increase the antenna performance was to use a natural dielectric material. In this research, a waveguide antenna was designed by inserting a natural dielectric material, an FR-4-Epoxy (? = 4,3 in the simulator) into a waveguide with a width of 72 mm, a height of 34 mm, and a length of 50 mm. The properties of the mode waveguide antenna were modified by slightly varying the position of the dielectric material and adding an initial thickness of 1.6 mm. The excitation of the waveguide was configured using mode. The Observed paramters in this research are (return loss) and radiation parameters (gain and directivity). On the simulation shows that the best performance of the waveguide antenna was obtained when the dielectric position is 2 mm from the connector and thickness 3,2 mm. The simulation also generates the parameter of -22,8 dB with gain and directivity was 5,77 and 1,799 respectively at a frequency 3 of GHz while from measurement the frequency was shifted at 3,15 GHz with -23,05 . The result of this research shows that the addition of dielectric material to the waveguide antenna as a resonator will affect the antenna parameters this is due to the nature of the dielectric material which has a special permittivity value that changes the nature of the medium of wave propagation propagating on the antenna. From the observations in the simulation stage, the closer the position of the material to the connector and the thicker the material, the better the return loss, even though it slightly shifts the working frequency of the antenna from the initial frequency. Manufacturing process was important in the development of antenna technology in order to obtain the antenna optimal performance. One of the approaches to increase the antenna performance was to use a natural dielectric material. In this research, a waveguide antenna was designed by inserting a natural dielectric material, an FR-4-Epoxy (? = 4,3 in the simulator) into a waveguide with a width of 72 mm, a height of 34 mm, and a length of 50 mm. The properties of the mode waveguide antenna were modified by slightly varying the position of the dielectric material and adding an initial thickness of 1.6 mm. The excitation of the waveguide was configured using mode. The Observed paramters in this research are (return loss) and radiation parameters (gain and directivity). On the simulation shows that the best performance of the waveguide antenna was obtained when the dielectric position is 2 mm from the connector and thickness 3,2 mm. The simulation also generates the parameter of -22,8 dB with gain and directivity was 5,77 and 1,799 respectively at a frequency 3 of GHz while from measurement the frequency was shifted at 3,15 GHz with -23,05 . The result of this research shows that the addition of dielectric material to the waveguide antenna as a resonator will affect the antenna parameters this is due to the nature of the dielectric material which has a special permittivity value that changes the nature of the medium of wave propagation propagating on the antenna. From the observations in the simulation stage, the closer the position of the material to the connector and the thicker the material, the better the return loss, even though it slightly shifts the working frequency of the antenna from the initial frequency.